Split Syntheses: Introducing Bottom-Up Control over Aluminum in SSZ-13 and ZSM‑5 Zeolites - Robijns, Sven; Devos, Julien; Baeckelmans, Beatrice; De Frene, Tom; Torka Beydokhti, Mostafa; de Oliveira-Silva, Rodrigo; De Witte, Niels; Sakellariou, Dimitrios; Van Assche, Tom R. C.; Dusselier, Michiel (JACS Au, 2025)
Zeolite synthesis is known as a difficult-to-control process, with many degrees of freedom that have a partially uncharted impact on the final product. Due to this, many zeolite scientists have regarded the initial mixing (aging) stage as the only time at which the chemical composition of a zeolite synthesis mixture can be impacted without heavily disrupting the delicate equilibria that are at play during crystallization. Recently, however, this view has started to change, with innovative techniques such as charge density mismatch or electro-assisted synthesis showing that the addition of new elements to the reactor midsynthesis might lead to new and surprising outcomes. In this manuscript, we show that by intermittent removal of certain fractions, notably Al-rich solids or Si-rich liquids, from the reaction medium during an interzeolite conversion from FAU-to-CHA (and FAU-to-MFI), one can control the Si/Al ratio of the final product, without heavily impacting the reaction time, particle size, or divalent cation capacity of the final product. This approach was named “split synthesis” and has led to several insights. By removing some Si-rich liquid phase after 40 min of synthesis, the Si/Al ratio of the daughter zeolite was lowered to a value of 20 (starting from 40), while the divalent cation capacity, a performance indicator for several acid and metal-catalyzed reactions, was kept maximized. On the other hand, when Al-rich solids were removed after 40 min (and in some cases colloidal silica was supplemented), we were able to rapidly synthesize small SSZ-13 zeolites with Si/Al ratios up to 180. These high-Si SSZ-13 zeolites had particle sizes in the range 100–150 nm and are traditionally difficult to crystallize in hydroxide medium. They showed a great olefin yield (6%) in the conversion of CO2 and H2 with ZnZrOx as cocatalyst.